PROFIL BERPIKIR ALJABAR SISWA SMP DALAM MENYELESAIKAN MASALAH MATEMATIKA DITINJAU DARI KECEMASAN MATEMATIKA - Latifatul Fajriah; Dwi Juniati; Rooselyna Ekawati (IKIP Siliwangi, 2022)
This research is a type of qualitative descriptive research that aims to describe algebra thinking skills of student SMP in solving mathematic problem review from mathematic anxiety. Two subject were selected through of provision of mathematic anxiety questionnaire (AKM) and mathematical ability test (TKM) in class VII-B of MTs Hidayatun Najah Tuban. The instrument used for problem solving test (TPM), and interview guide. The data analysis technique uses data reduction, data presentation, and drawing conclusions. The result show that low anxiety student do all algebraic thinking activities, meanwhile high anxiety student don’t make algebraic thinking activities.